Dynamic prediction of overhead transmission line ampacity based on the BP neural network using Bayesian optimization - Sun, Yong; Liu, Yuanqi; Wang, Bowen; Lu, Yu; Fan, Ruihua; Song, Xiaozhe; Jiang, Yong; She, Xin; Shi, Shengyao; Ma, Kerui; Zhang, Guoqing; Shen, Xinyi (Frontiers in Energy Research, 2024)
Traditionally, the ampacity of an overhead transmission line (OHTL) is a static value obtained based on adverse weather conditions, which constrains the transmission capacity. With the continuous growth of power system load, it is increasingly necessary to dynamically adjust the ampacity based on weather conditions. To this end, this paper models the heat balance relationship of the OHTL based on a BP neural network using Bayesian optimization (BO-BP). On this basis, an OHTL ampacity prediction method considering the model error is proposed. First, a two-stage current-stepping ampacity prediction model is established to obtain the initial ampacity prediction results. Then, the risk control strategy of ampacity prediction considering the model error is proposed to correct the ampacity based on the quartile of the model error to reduce the risk of the conductor overheating caused by the model error. Finally, a simulation is carried out based on the operation data of a 220-kV transmission line. The simulation results show that the accuracy of the BO-BP model is improved by more than 20% compared with the traditional heat balance equation. The proposed ampacity prediction method can improve the transmission capacity by more than 150% compared with the original static ampacity.